Analisis Pengendalian Kualitas Super Absorbent Polymer Dengan Menggunakan Metode Six Sigma - Rosihin, Rosihin; Mujaddid Ulinnuha, Laksamana; Cahyadi, Dadi (Universitas Serang Raya, 2017)
Quality control is an effort to increase customer satisfaction and minimize damage. Super Absorbent Polymer which is a product as a raw material for making baby diapers / elderly and sanitary napkins. In Super Absorbent Polymer, defects usually found in the colour contamination that there is a dark colour on the product, print labels mistakes and packaging defects. This study aims to determine the value of DPMO and sigma level, identify the efforts which is taken to reduce disability, identify the types of disability, and find the main factors causing disability. Six Sigma method is used to analyze data with define, measure, analyze, improve and control. The quantitative data obtained by direct observation of quality problems. By using the method of six sigma can be seen that the quality of the resulting product is quite good that is 3.07 sigma with a damage rate of 58,624 for a million production (DPMO). The three highest defect product causes are color contamination of 93.34%, misprint of 3.55%, and packaging damage as much as 3.11%. The main factor causing defects is the engine factor for the type of colour contamination defect,. The type of improper defects in the packaging labels and main factor for the packaging defects is the human factor.kecacatan rusaknya kemasan faktor utama ialah faktor manusia.